"M@dNotes Project". Giving colour to Grey Literature - Miguel Pizzanelli Báez; Marc Jamoulle (Sociedade Brasileira de Medicina de Família e Comunidade, 2019)
Sharing the results of research and scientific production is crucial for the survival and development of all disciplines. Health information is becoming uncertain and powerful economic interests disrupting medical information has triggered a loss of credibility. M@dNotes project (in Spanish NotasL@cas), is the by-product of nonprofit collaborative international knowledge network with participation of students, general practitioners, family physicians, and healthcare workers. One of the aims of this network is to discuss the validity of the information available on sensitive subjects and build a knowledge exchange network inside a community of practice. It has been created to share different materials excluded from traditional academic publishing and commercial distribution channels: monographic reports, commented articles, files with references searches. These materials product of learning process are qualified with an appropriate level because there were submitted to a peer review or judged by a scientific committee to get an approval. Includes an indexing method (Q Codes and ICPC) to manage and retrieve the materials received. The project provides a particular folder to upload and share the documents. A web blog is the dissemination friendly tool or interface to share and retrieve the documents available in the network. Through a facility in the cloud, it is possible to access an excel file with all the materials shared, codes assigned and the hyperlink to get a pdf file of each material.